Analysis Of Non-Cash Payment Control Systems On Revenue At PT Marga Sarana Jabar - Trisna, Ayu; Sianipar, Hesti Herawati (Institut Bisnis dan Informatika Kesatuan, 2023)
PT Marga Sarana is companies operating in the field service that is as administration and service service road toll. In giving service to users road effective and efficient toll road for customers feel comfortable as well as make it easier accessibility road toll, then required system payment in a way non-cash ( e -tool). System Many non- cash payments profitable and giving convenience to user her, especially For company in do A activity business his shaped non- cash payment, will more A little risk its implementation compared to with system payment cash. System systemized non - cash payments with Good will produce A effective income and expenses efficient operation. Because of that, company must need A internal control, especially on revenue company. Research purposes This For know system non- cash payment to control income. Writer do research at PT. Marga Sarana Jabar which is located at Plaza Sentul, Jl. Bogor Outer Ring Road, Cadas Ngampar, West Bogor. In running study This researcher do approach descriptive qualitative. Result of study this, that system control non- cash payment Already done with Good so that increase quality revenue and efficiency to burden operation company although Still must There is repair. Keywords: Non-Cash, Internal Control System, Revenue